The impact of ferroptosis and ferroptosis-related non-coding RNAs on breast cancer progression - Liu, Wenhui; Jiang, Chenjun; Ma, Yun; Wang, Wentao; Peng, Jing; Ma, Weiqing; Xu, Shuxin; Wu, Duoming (Frontiers in Cell and Developmental Biology, 2024)
Ferroptosis, distinct from apoptosis, is primarily characterized by the accumulation of iron-dependent lipid peroxides (LPO) and reactive oxygen species (ROS). This process plays a pivotal role in the pathophysiology of various diseases and has recently emerged as a promising therapeutic strategy in oncology, garnering significant attention. Non-coding RNAs (ncRNAs), including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), serve as crucial regulators in numerous biological processes, particularly in cancer initiation and progression. Increasing research efforts are focused on targeting ferroptosis through modulation of these ncRNAs. This review provides an overview of the mechanisms underlying ferroptosis and explores the roles of ncRNAs in breast cancer (BC) and its regulation. Furthermore, we examine the interactions between ferroptosis and ncRNAs in BC, aiming to identify potential therapeutic targets for BC treatment.